2023
DOI: 10.1111/ijcs.12936
|View full text |Cite
|
Sign up to set email alerts
|

Consumer neuroscience on branding and packaging: A review and future research agenda

Abstract: In an environment of extreme competition, it is essential to have a differentiated brand that adds value to consumer communications through packaging. Neuroscience research techniques have undergone remarkable development, facilitating the understanding of consumer brain mechanisms in the choice and purchase decision‐making process. This article presents the first systematic and specific literature review of the branding and packaging from the consumer neuroscience viewpoint. The main objective is to carry out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 143 publications
(311 reference statements)
0
2
0
2
Order By: Relevance
“…En concreto, muchos de estos estudios se han interesado en el análisis del branding y el packaging. Destaca la reciente publicación de la revisión de Rodríguez et al, (2023), donde los autores analizan de modo pormenorizado los principales hallazgos encontrados en estas áreas desde el campo de la neurociencia del consumidor. Entre otros aspectos, destacan que, ciertos correlatos biométricos confirman que la conductancia de la piel se reducía cuando los consumidores veían la marca que más les gustaba (Walla et al, 2011).…”
Section: Neurociencia En La Comunicación Y El Marketing De Alimentosunclassified
See 1 more Smart Citation
“…En concreto, muchos de estos estudios se han interesado en el análisis del branding y el packaging. Destaca la reciente publicación de la revisión de Rodríguez et al, (2023), donde los autores analizan de modo pormenorizado los principales hallazgos encontrados en estas áreas desde el campo de la neurociencia del consumidor. Entre otros aspectos, destacan que, ciertos correlatos biométricos confirman que la conductancia de la piel se reducía cuando los consumidores veían la marca que más les gustaba (Walla et al, 2011).…”
Section: Neurociencia En La Comunicación Y El Marketing De Alimentosunclassified
“…Según los autores, destacan la necesidad de tener en cuenta el diseño experimental, la naturaleza de los estímulos y el contexto de los sujetos. Asimismo, y a pesar del gran número de académicos que investigan sobre branding y packaging utilizando herramientas de neuromarketing (Stasi et al, 2018), se ha comprobado que es una disciplina relativamente nueva (Rodríguez et al, 2023), donde no es tan frecuente encontrar estudios sobre la identidad y la imagen visuales de marca. Además, se requiere un esfuerzo conjunto con el fin de conseguir estandarizar el contexto teórico y metodológico para avanzar en la disciplina.…”
Section: Conclusionesunclassified
“…Multiple facets of product design, particularly in the domain of packaging, have been gradually embracing innovative evaluation techniques. Notably, this shift has witnessed a significant acceleration in recent years [ 24 ]. Several studies, primarily focused on neurosciences, have demonstrated the effectiveness of neuro-techniques in analyzing the perception of the aesthetics, brands, packaging, and pricing of products.…”
Section: Introductionmentioning
confidence: 99%
“…Slanzi et al [5] evaluated the click intentions of network users by merging pupil dilation and EEG responses based on physiological analysis. Rodriguez et al [15] systematically explained the brand and packaging of products from a neuroscientific perspective. We can interpret the brain and psychological activities of users when they browse specific advertisement information on a page, including attention level, memory, and emotional response.…”
Section: Introductionmentioning
confidence: 99%